Menjadi Laskar Kristus yang Siap Menderita: Pembinaan Remaja-Pemuda HKBP Paranginan - Simanjuntak, Pahala; Pardede, Petrus N. B.; Situmorang, Dedi S. P. (Bulletin of Community Engagement, 2022)
Youth and adolescent delinquency is increasingly rampant to the point that it has become something to worry about nowadays. Church youth and teenagers as the next generation need to be given spiritual formation to anticipate youth and adolescent delinquency. It is within this framework that STT HKBP provides guidance to youth and teenagers as well as at HKBP Paranginan. This training aims to provide knowledge to youth and teenagers regarding their identity as Warriors of Christ who are ready to suffer. This coaching method involves active participation from youth and teenagers at HKBP Paranginan. This formation received an immediate positive response because it included a new understanding of the meaning of the Soldiers of Christ who are ready to suffer. Keywords: Financial Literacy, Digital Marketing, Financial Technology, SMEs Performance